Adsorption and removal of organophosphorus pesticides from Chinese cabbages and green onions by using metal organic frameworks based on the mussel-inspired adhesive interface. (1st November 2022) - Liu, Guangyang; Zhang, Xuan; Lu, Meng; Tian, Mingshuo; Liu, Yuan; Wang, Jian; Li, Lingyun; Li, Tengfei; Chen, Ge; Xu, Donghui
Highlights: Fe3 O4, PDA, and MIL-101(Fe) nanoparticles were uniformly coated on the g-C3 N4 surface. Fe3 O4 -g-C3 N4 -PDA@MIL-101(Fe) exhibited porous 3D structure and high surface area. The composite could effectively adsorb organophosphorus pesticides (OPs). The OPs in Chinese cabbage and green onion samples were removed efficiently by MSPE. Abstract: Based on the mussel-inspired adhesive interface (Fe3 O4 -g-C3 N4 @PDA), a novel bionic metal–organic framework (Fe3 O4 -g-C3 N4 -PDA@MIL-101) was successfully prepared. The composite featured a high specific surface area and a multi-microchannel structure, as well as strong thermochemical stability. The structural property of Fe3 O4 -g-C3 N4 -PDA@MIL-101(Fe) was characterized, and the results indicated that Fe3 O4, PDA, and MIL-101(Fe) were uniformly coated on the g-C3 N4 surface. The adsorption and desorption of organophosphorus pesticides with Fe3 O4 -g-C3 N4 -PDA@MIL-101(Fe) were evaluated by batch experiments. This composite showed high adsorption efficiency and selective removal of coralox, phosalone, and chlorpyrifos. Under the optimal conditions, three organophosphorus pesticides were adsorbed from Chinese cabbage and green onion samples with Fe3 O4 -g-C3 N4 -PDA@MIL-101(Fe). The analytical method exhibited high sensitivity (LOD, 0.19–2.34 μg/L; LOQ, 0.65–7.82 μg/L), excellent practicality, and good stability, suggesting that Fe3 O4 -g-C3 N4 -PDA@MIL-101 was an ideal candidate magnetic adsorbent for the removal of organophosphorus pesticides in Chinese cabbage and green onion samples.